The soil surface insect diversity of oil palm plantation at various distances from the forest - Haneda, Noor Farikhah; Rahmawati, Ismi Arsilah; Amanda, Ananta Kusuma; Anggarawati, Sri Hastuti (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2024)
Oil palm plantations have always been attached to the issue of ecosystem degradation, both biotic and abiotic. Insects as one of the biotic factors in the ecosystem often have important roles such as pollinating agents and soil improvers. This study explored the effect of distance between oil palm plantations and forests on the diversity of soil surface insects. This study used the pitfall trap method to collect insect samples and analyze ecosystem richness, diversity, evenness, and similarity. It was found that differences in distance had an impact on insect abundance, composition and diversity. The ecotone ecosystem, which is at the closest distance to the forest, showed higher insect abundance and richness compared to the oil palm ecosystem. This creates higher values of ecosystem diversity and similarity between the two ecosystems. However, distance may also limit insect movement between ecosystems. Results from the study may provide new insights into the distance factor in understanding the ecological dynamics of insects between oil palm and forest ecosystems, which may contribute to more effective conservation planning. Keywords: Distance, ecotone, forest, insects, oil palm